The Effect of Work Ethic on Job Performance, Mediated by Employee Discipline, at the Kapuas Regency Education Office - Agustin; Misransyah Akos; Moh. Heru Budihantho; Septeria Noor Yuliannisa (Universitas Muhammadiyah Makassar, 2026)
This study aims to analyze the effect of work ethic on employee job performance, with work discipline as a mediating variable, at the Kapuas Regency Education Office. The research problem stems from fluctuations in employee discipline levels, which have the potential to affect organizational performance. This study employs a quantitative approach with an associative design. The study population consists of 97 employees, with a sample of 78 respondents determined using the Slovin formula with a 5% margin of error and stratified random sampling. Data were collected via a questionnaire using a Likert scale and analyzed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The results indicate that work ethic significantly influences work discipline, work discipline significantly influences work performance, and work ethic significantly influences work performance. Furthermore, work discipline was found to mediate the relationship between work ethic and employee work performance. These findings indicate that enhancing work ethic values must be accompanied by strengthening disciplinary behavior as a mechanism that transforms value orientation into measurable performance. This study provides a theoretical contribution to strengthening the value–behavior–performance relationship model in the public sector, as well as practical implications for human resource management in local government agencies.